Transformational Leadership and Employee Work Engagement in Public Sector Organizations: The Mediating Roles of Job Satisfaction and Employee Motivation - Inayah Inayah; Tetra Hidayani; Siti Maria (Economics and Digital Business Review, 2026)
This study aims to examine the effect of transformational leadership on work engagement through job satisfaction and employee motivation at the Department of Cooperatives and SMEs of East Kutai Regency. This research uses a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 61 employees using a saturated sampling technique. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with the assistance of SmartPLS software. The results show that transformational leadership has a positive and significant effect on job satisfaction, employee motivation, and work engagement. However, job satisfaction and employee motivation do not have a significant direct effect on work engagement. Furthermore, job satisfaction does not mediate the relationship between transformational leadership and work engagement. Meanwhile, employee motivation partially mediates the relationship between transformational leadership and work engagement. These findings indicate that transformational leadership plays an important role in increasing employee work engagement. Leaders who are able to provide inspiration, support, and clear direction can encourage higher levels of employee involvement in their work. Therefore, organizations need to strengthen the implementation of transformational leadership to improve employee engagement in the workplace.